A Detailed Review Investigating the Mathematical Modeling of Solar Stills - Ayoobi, Ahmadreza; Ramezanizadeh, Mahdi (Frontiers in Energy Research, 2022)
Nowadays, an extra major problem is providing potable water for humans, especially in rural and remote regions. In the last few decades, the method of providing potable water using solar radiation has proved that it can be replaced with other methods without their negative impacts. Solar still is a solution and very attractive alternative to still non-potable water without adverse consequences on ecosystems. Researchers have presented results of their investigations in the journals as the experimental, numerical, and analytical forms through the study of solar stills performance in native climatic conditions. This paper carries out an extensive review of the modeling processes in solar stills and thermal models proposed and derived for different types of solar stills and their modifications recommended to enhance efficiency and performance in recent years. During the selection of appropriate geometry and belongings components, this evaluation demonstrated that numerous designs and characteristics are useful in productivity and efficiency. According to the reviewed results, the definition of concentration ratio is a fundamental concept for evaluating the evaporative heat transfer coefficient in relation to the convective heat transfer coefficient. Employing phase change materials, the results revealed that a large mass of PCM produces less solar still's productivity, whereas increasing the PCM to water mass ratio from 10 to 100 reduced productivity by up to 30%. Using a parabolic concentrator showed that the productivity was increased 56 and 38.5% in the winter and summer, respectively.